2011
DOI: 10.1111/j.1365-2966.2011.19386.x
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of a molecular cloud core to stellar densities: the formation and evolution of pre-stellar discs

Abstract: We report results from radiation hydrodynamical simulations of the collapse of molecular cloud cores to form protostars. The calculations follow the formation and evolution of the first hydrostatic core/disc, the collapse to form a stellar core, and effect of stellar core formation on the surrounding disc and envelope. Past barotropic calculations have shown that rapidly rotating first cores evolve into ‘pre‐stellar discs’ with radii up to ∼100 au that may last thousands of years before a stellar core forms. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 57 publications
1
106
0
Order By: Relevance
“…While pure hydrodynamical simulations (e.g. Bate 2011;Tomida et al 2010a) and some radiation iMHD (RMHD) calculations (Tomida et al 2010b) found a similar result with a flattened first core, other RMHD studies (Commerçon et al 2010) did not find flattened cores in the case µ = 5. As a result of the additional magnetic support, the free-fall (thus core formation) timescale is twice longer for µ = 2 than for µ = 5 .…”
Section: First Larson Corementioning
confidence: 78%
“…While pure hydrodynamical simulations (e.g. Bate 2011;Tomida et al 2010a) and some radiation iMHD (RMHD) calculations (Tomida et al 2010b) found a similar result with a flattened first core, other RMHD studies (Commerçon et al 2010) did not find flattened cores in the case µ = 5. As a result of the additional magnetic support, the free-fall (thus core formation) timescale is twice longer for µ = 2 than for µ = 5 .…”
Section: First Larson Corementioning
confidence: 78%
“…At ages of a few Myr, the vast majority of an object's luminosity comes from the release of internal gravitational energy, so the onset of hydrogen burning would have a negligible effect on overall luminosity (Chabrier & Baraffe 1997). We note, however, that hydrodynamical cluster collapse simulations (Bate 2009) are in good agreement with the stellar IMF and stellar CMF, but overproduce the number of brown dwarfs unless radiative feedback is incorporated into the model (Bate 2011). The last model produces a cluster of stars and brown dwarfs whose statistical properties are very similar to those of observed young clusters, suggesting that radiative feedback is indeed an important mechanism in brown dwarf formation.…”
Section: More Evidence For a Discontinuity At The Hydrogen Burning LImentioning
confidence: 99%
“…They therefore allow for an arbitrary overlap of the stellar and brown dwarf components of the IMF, thus allowing for a smooth turnover. In light of our companion mass distribution for low-mass stars (Figure 10), new developments in the hydrodynamical simulations of star cluster formation (Bate 2009(Bate , 2011, and new observations of young stellar clusters (Kraus et al 2008(Kraus et al , 2011Evans et al 2012), we re-examine the nature of the IMF discontinuity at masses close to the hydrogen burning limit.…”
Section: More Evidence For a Discontinuity At The Hydrogen Burning LImentioning
confidence: 99%
“…Only the central part of the first core alone becomes the protostar, whereas the remainder rotates around the protostar. Thus, the protostar at its formation epoch is already enclosed by a large-scale disc-like structure evolved from the first core or its remnant (Bate 1998(Bate , 2011Machida et al 2010a;Machida & Matsumoto 2012). Since the remnant of the first core or circumstellar disc is more massive than the protostar just after the protostar formation, fragmentation can occasionally occur in the disc (Inutsuka et al 2010;Inutsuka 2012).…”
Section: Effects Of First Hydrostatic Corementioning
confidence: 99%